KEHIDUPAN SOSIAL EKONOMI PETANI KELAPA (1999-2012). - Arizah, Mulroni; Yulia, Refni; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
Social-Economic Living of Cocoa Farmer in Linggo Sari Baganti Subdistrict year 1999-2012. Thesis. History Education. STKIP PGRI West Sumatera, 2014. This thesis discusses about Sosial Economic Living of Cocoa Farmer in Linggo Sari Baganti Subtdistrict. The problems of this research are: (a ) How is the background of the appearing of cocoa farmer in Linggo Sari Baganti Subdistrict. ( b) How is the development of cocoa farmer in Linggo Sari Baganti Subdistrict. ( c ) How is the dynamics of Sosial Economic Living of Linggo Sari Baganti society as cococa farmer. The purpose of this research is to describe sosial economic Living of cococa farmer in Linggo Sari Baganti subdistrict from 1999 to 2012. This research belongs to history research, so that this study follows history method: (1) Heuristic, that is searching and collecting information from primary and secondary sources. (2) sources critis covers internal and external critic. By doing experiment to the authenticity of sources or data determined. (3) Interpretation, that is reinterpreting the data that has ben collected. (4) Historiography, that is the presentation of research result in form of thesis. This research result show that cocoa garden has given significant changes to the sosial economic living of cocoa farmer, that is the increasing of societyâs earning in Linggo Sari Baganti subdistrict. The changes are: the first, daily needs of farmer are fulfilled. The second, the farmer can to be spent on valuable things such as gold, house furnitures and previous one, for example: from semi-permanent to permanent. The forth, farmers become more enthusiastic to register their children to the school. From elementary school, junior high school, seniorhigh school until university/ college. The fifth, increasing their their consciousness oftheir health because they have much money to take care of their of healt.